Tritium contamination and hydrological transport in the Shagan River: An isotope hydrology study - Togzhan Toktaganov; Ainur Mamyrbayeva; Аssan Aidarkhanov; Almira Aidarkhanova; Almira Raimkanova (PLoS ONE, 2025)
This paper presents the results of a study of the distribution of the radionuclide tritium (3H) and stable isotopes of hydrogen and oxygen in the Shagan River. The Shagan River flows through the territory of the ‘Balapan’ test site and is the longest watercourse on the territory of the former Semipalatinsk Test Site (STS), and is also a left-bank tributary of the Irtysh River. The isotope hydrology method (2H and 18O) was used to determine the conditions for the formation of tritium-contaminated waters in the Shagan River. The study revealed certain sections of the river, especially at distances of 5, 10 and 14 km from the source, where elevated concentrations of tritium and stable isotopes indicated a significant influx of groundwater. A combined analysis of the isotopic composition and mineralization helped to assess the role of evaporation and identify hyporheic zones that contribute to the redistribution of radionuclides. At the confluence of the Shagan and Irtysh rivers, tritium activity does not exceed the intervention level of 7600 Bq/l recommended by the World Health Organization and the International Atomic Energy Agency for drinking water.